Effect of size and surface area of graphene nanoplatelets on the thermomechanical and interfacial properties of shape memory multiscale composites. Issue 12 (13th August 2022) - Tiwari, Nilesh; Shaikh, A. A.
ABSTRACT: The availability of surface area on the structure of nanoparticles significantly regulates the interfacial bonding between the nanofillers and polymer matrix, which inherently govern the mechanical and thermomechanical properties of the fabricated composites. An investigation of shape memory multiscale composite (SMMC) with incorporation of different sizes of graphene in the carbon fiber-reinforced polymer composite (CFRP) was performed. Mechanical and thermomechanical properties of SMMC studied through tensile testing and dynamic mechanical analysis, respectively, were improved with the increase in the surface area of the graphene nanoplatelets. The improvement in the interfacial bonding was noticed in the images from the scanning electron microscopy due to enhanced wettability of fibers and efficient load transfer at the matrix–fiber interphase. The investigation of shape memory parameters of SMMC, shape recovery and fixity, was performed through heat-activated bending tests. Appreciable shape fixity (96 ± 2%) and shape recovery (93 ± 2%) were achieved, which would not prohibit its probability of sophisticated smart material applications. Increase in the surface area of graphene nanoplatelets had a better influence on the tensile modulus of SMMC with a 30% higher elastic modulus than the unmodified CFRP, which subsequently enhanced the thermal response and storage modulus.